Failure phenomena in two-dimensional multi-fibre model composites: 5. A finite element study - van den Heuvel, PWJ; Wubbolts, M.K.; Young, R.J.; Peijs, T.
A three-dimensional (3D)finite element (FE)analysis of the stress concentration factor (SCF)around a broken fibre in a model composite has been performed. This model composite consisted of a planar array of five carbon fibres positioned in the centre of an epoxy tensile bar. Two cases were considered, namely the case of perfect fibre/matrix adhesion and the case of poor fibre/matrix adhesion. For the case of perfect fibre/matrix adhesion, a parametric study was performed to study the influence of the inter-fibre spacing, matrix plasticity, and the ratio of the matrix modulus (Em)to the fibre modulus (Ef)on the stress concentration around a fibre break. It was found that the SCF increases with an increase of the ratio Em/Ef, an increase of the matrix yield stress, and a decrease of the inter-fibre spacing. For the case of poor fibre/matrix adhesion, a parametric study was performed to study the influence of the debonded length and the coefficient of friction on the SCF. It was found that the SCF increases with a decrease of the debonded length and an increase of the coefficient of friction. More importantly, the results of the FE analysis were validated against experimental results obtained with Raman spectroscopy. In this validation three matrix systems with varying mechanical behaviour and two carbon fibres with different levels of fibre/matrix adhesion were considered. In general, good agreement between the experimental stress situation and the calculated stress situation of the fibres in the model composite was found. At relatively small inter-fibre spacings, however, the FE analysis predicts SCFs slightly lower than experimentally measured
Keywords: COMPOSITES; STRESS CONCENTRATIONS; FINITE ELEMENT ANALYSIS (FEA); RAMAN SPECTROSCOPY